3.2q-4.1-4.6q=-2.4q-3.2

Simple and best practice solution for 3.2q-4.1-4.6q=-2.4q-3.2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3.2q-4.1-4.6q=-2.4q-3.2 equation:


Simplifying
3.2q + -4.1 + -4.6q = -2.4q + -3.2

Reorder the terms:
-4.1 + 3.2q + -4.6q = -2.4q + -3.2

Combine like terms: 3.2q + -4.6q = -1.4q
-4.1 + -1.4q = -2.4q + -3.2

Reorder the terms:
-4.1 + -1.4q = -3.2 + -2.4q

Solving
-4.1 + -1.4q = -3.2 + -2.4q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '2.4q' to each side of the equation.
-4.1 + -1.4q + 2.4q = -3.2 + -2.4q + 2.4q

Combine like terms: -1.4q + 2.4q = 1q
-4.1 + 1q = -3.2 + -2.4q + 2.4q

Combine like terms: -2.4q + 2.4q = 0.0
-4.1 + 1q = -3.2 + 0.0
-4.1 + 1q = -3.2

Add '4.1' to each side of the equation.
-4.1 + 4.1 + 1q = -3.2 + 4.1

Combine like terms: -4.1 + 4.1 = 0.0
0.0 + 1q = -3.2 + 4.1
1q = -3.2 + 4.1

Combine like terms: -3.2 + 4.1 = 0.9
1q = 0.9

Divide each side by '1'.
q = 0.9

Simplifying
q = 0.9

See similar equations:

| 1+p+5+p=-2 | | 6r(2r-1)= | | 5x+24=12x+60 | | 6m+10=25-m | | 5x+11=12x+60 | | (5x^2-x-7)+(2x^2+3x+4)= | | 20e+50f=8(40) | | 22x-26x=10-14 | | -10-8x=-110+6 | | 3x-5y-4y+9x+2= | | 2xa-11=-5 | | 5x=48+2x | | (5x+3o)+9o= | | -3(4)+-2=x | | -(x-1)-4(x-3)=58 | | -0.2(-15x-10)=10 | | -7(4)+15=x | | z(2z-9)(z+4)=0 | | x^2+kx-9=0 | | 5=4(x-4)+3-3x | | 30+y=3y | | 12x+4+13x-4=180 | | (m-1)x^2+mx+2m=0 | | n+(n+1)+(n+2)+(n+3)=1368 | | 30+y=6y | | 6x+8-5x=14-15x-16 | | 6x/5+12x=3(5/2) | | 3b^2+20b+31=6 | | x^4+10x^3-59x^2+40x+60=0 | | 12y-8=-4 | | 34x-543=321 | | 2x-34=87 |

Equations solver categories